PP148 The Impact Of Health Technology Wales Guidance For Autologous Hematopoietic Stem Cell Transplantation: Two Years Post-Publication. (23rd December 2022) - Elston, Lauren; Hughes, Sophie; Glarou, Eleni; Myles, Susan
Abstract : Introduction: Evaluating the impact of health technology assessment (HTA) is vital to measure its contribution to health and social care decision-making and improving citizen outcomes. Health Technology Wales (HTW) is a HTA body committed to evaluating the impact of our work. Here we present HTW's impact evaluation approach with a case study for autologous hematopoietic stem cell transplantation (AHSCT) for highly active relapsing remitting multiple sclerosis (RRMS). Methods: Using an outcomes-focused approach based on contribution analysis, HTW has worked with an external evaluation organization to develop a framework to measure the impact of our work. Data on impact was collected from both qualitative and quantitative sources, including social media metrics, surveys, and informal feedback from stakeholders. We engaged with various stakeholders, including clinicians, academics, patient organizations and other HTA bodies. Results: The technology appraisal and guidance were published in July 2020, recommending AHSCT for routine adoption to treat highly active RRMS. Patient groups welcomed the appraisal findings as an important step forward in recognising the needs of people with RRMS and felt that "people living with MS were listened to throughout the process". Following publication online, the guidance has had approximately 500 views, and featured on the MS Trust website and in several news articles. The Welsh Health Specialist Services Committee, a commissioning body in Wales, recommended AHSCT for RRMS as a 'high priority' for funding in the WHSSC Integrated Commissioning Plan 2021-22. Conclusions: Since its publication, we have been able to prospectively capture the impact of this guidance through various stakeholders groups and sources. Overall, responses have been positive and the guidance has supported decision makers in Wales. Ongoing evidence capture, including through HTW's adoption audit processes, will add further understanding to the potential impact of our work.